An implementation study on Hazard Identification and Risk Assessment (HIRA) technique in the Critical Care Unit of a Tertiary Care Hospital - Rajvinder Kour1 , Ankit Singh2, Neha Ahire2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the studied hospital an increased number of adverse events were noted in the critical care unit (CCU)department of the tertiary care hospital in the last three months. Hence, a risk management technique, HazardIdentification and Risk Assessment (HIRA) is applied to identify the hazards and to reduce the risk of theidentified hazards by administering suitable mitigation and the control programs. The study was carriedout for three months i.e from May 2019 to July 2019 and all the staff’s responses of the CCU departmentwere captured to prepare the list of the perceived hazards. Moreover, the risk matrix is prepared for theidentified hazards by the responses of the CCU staff captured under the categories probability and severity.The findings of the study conclude that the risk associated with hazards H12 (Hindrance in the movementof patients, staff and utilities due to obstructed corridors), H2 (Malfunctioning of Life-saving equipmentor patient monitoring Biomedical Equipment) and H3 ( The broken cable of equipment results in powerleakage, short circuit and the trip of electricity supply in the department). The suitable interventions for thesecan be increased frequency of safety rounds, widening of the corridors and restricting access to the patientmovement areas, and buffer stock for the life-saving devices.